Sistem Informasi Geografis (SIG) Sebaran LPD di Kota Denpasar Berbasis Web Menggunakan Framework Laravel - Ida ayu Utari Dewi; I Kadek Noppi Adi Jaya; I Dewa Kadek Laksana Digita (Universitas Pendidikan Ganesha, 2022)
Abstract-Technological developments in the information era which is very easy to obtain wherever and whenever the public must be able to make good use of it. In the Bali area there is an institution that helps the community in terms of financial services, namely the LPD. Even though information technology has been very developed, currently there are also deficiencies such as a mapping of LPD information. Where LPD information is still difficult to map, such as location, active status to the head of the LPD in office. Geographic information system (GIS) mapping is a very appropriate solution because it will provide location information about LPDs in Bali, especially in Denpasar City. Making a geographic information system for the distribution of LPDs in Denpasar City uses the Laravel framework. The Laravel framework is used because it has good capabilities and has a structured folder structure. By conducting this research, the public will know the location of the distribution of LPDs in Denpasar City along with the information. This research was conducted to produce useful information for information users to obtain the location of the distribution of LPDs in Denpasar City. The result of developing this geographic information system (GIS) is an information website for LPD distribution in Denpasar City. Keywords-component: technology, information, spread, gis, lpd